Front Cover. Issue 8 (11th July 2018) - Palmeirim, Ana Filipa; Benchimol, Maíra; Morante‐Filho, José Carlos; Vieira, Marcus Vinícius; Peres, Carlos A.
Abstract : The cover image, by Ana Filipa Palmeirim et al ., is based on the Biodiversity Research Ecological correlates of mammal β‐diversity in Amazonian land‐bridge islands: from small‐ to large‐bodied species, https://doi.org/10.1111/ddi.12749 . Photo Credit: Ana Filipa Palmeirim.